2017
DOI: 10.1016/j.cmet.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A Methyl-Balanced Diet Prevents CRF-Induced Prenatal Stress-Triggered Predisposition to Binge Eating-like Phenotype

Abstract: Binge eating (BE) is a common aberrant form of eating behavior, characterized by overconsumption of food in a brief period of time. Recurrent episodes of BE constitute the BE disorder, which mostly affects females and is associated with early-life adversities. Here, we show that corticotropin releasing factor (CRF)-induced prenatal stress (PNS) in late gestation predisposes female offspring to BE-like behavior that coincides with hypomethylation of hypothalamic miR-1a and downstream dysregulation of the melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…Contrary to our expectations, PNS females gained similar weight ( Figure 4 B), consumed less WD during the habituation period ( Figure 4 C) when compared to CTRL group and overall did not develop BE ( Figure 4 D). Thus, the PNS females’ response appears to reflect anhedonia rather than the expected compulsivity observed in a different model of late gestational stress [15] . From a metabolic perspective, PNS females exposed to this protocol showed decreased food intake post-recovery, lowered metabolic rate, and similar activity in comparison to CTRLs ( Figure 4 E).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Contrary to our expectations, PNS females gained similar weight ( Figure 4 B), consumed less WD during the habituation period ( Figure 4 C) when compared to CTRL group and overall did not develop BE ( Figure 4 D). Thus, the PNS females’ response appears to reflect anhedonia rather than the expected compulsivity observed in a different model of late gestational stress [15] . From a metabolic perspective, PNS females exposed to this protocol showed decreased food intake post-recovery, lowered metabolic rate, and similar activity in comparison to CTRLs ( Figure 4 E).…”
Section: Resultsmentioning
confidence: 84%
“…Interestingly, late PNS and HF diet increases adiposity in female, but not male rats [52] . Late PNS further increases susceptibility to BE in female mice [15] and to ABA in a subset of passively stress-coping female rats [52] . In contrast, when PNS takes place during the whole gestational period, the females’ innate susceptibility to ABA disappears [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to prenatal stress or GCs has been associated with persisting changes in DNAm in neuronal tissues and cells. In animal models of prenatal stress, lasting changes in DNAm in the hypothalamus or hippocampus have been reported in specific candidate genes (21,22). Another set of studies has reported the impact of chronic administration of GCs on DNAm in adult mouse hippocampus as well as in a rodent primary neuronal cell line, both in candidate genes (17,23) and at a genome-wide level (18,24).…”
Section: Significancementioning
confidence: 99%
“…Thus, blocking CRH receptors modulates partner preference in prairie voles (Lim et al, 2007) and alters nicotine-use behaviors (Marcinkiewcz et al, 2009). In contrast, CRH microinjections in the NAc amplify incentive salience of Pavlovian cues for rewards in rodents (Peciña et al, 2006), a potential mechanism for stress-triggered drug relapse and stress-related binge eating (Schroeder et al, 2017). In stress-naïve rodents, microinjections of CRH into the NAc induces a conditioned place preference and increases local dopamine release (Lemos et al, 2012).…”
mentioning
confidence: 99%